ABOUT THE INTEGRATION OF B-LEARNING IN EPP TO REINFORCE LEARNER AUTONOMY - Irina Argüelles Álvarez (Revista de Lingüística y Lenguas Aplicadas)
This article builds on one particular initiative that has been developed for over a year and brings blearning to the English for Professional Purposes classroom within a learner-centred context. The first section is dedicated to the description of the conditions that have framed the experience. Then the steps taken to adapt the materials of the subject "Professional Communication" to the b-learning environment MOODLE are addressed. This part also examines the evolution of the subject towards autonomous language learning goals and a negotiated syllabus design more suitable for b-learning. The third part of the paper outlines the results from the actual learning in the virtual environment of a pilot group of students. Qualitative data concerning the benefits of MOODLE within an autonomous learning context are presented. To conclude, it is suggested that prior analysis of each particular teaching situation is very important to decide whether MOODLE will in fact fulfil previous expectations.